Transmitted Torque Analysis of Coaxial Magnetic Gears with Different Pole-Pair Numbers - Yi-Chang Wu; Mi-Ching Tsai; Hao-Pin Wu (Journal of ICT, Design, Engineering and Technological Science, 2019)
Transmitted torque is an important performance index of coaxial magnetic gears. This study focuses on the effects of pole-pair numbers on the maximum torque capacity and torque ripple of coaxial magnetic gearsOwing to the magnetic resistance between the pole piece and the medium of air; a torque ripple is generated during magnetic gear operation. In magnetic gear design, maximum torque capacity is considered the higher, the better, and the torque ripple should be the lower, the better. A commercial Finite-element analysis software AN-SYS/Maxwell 2D is applied to simulate the transmitted torque and torque ripple of coaxial magnetic gears by solving the magnetic field, and mechanical motion coupled models. Model parameters, including size and inertia, are designed via the Autodesk/Inventor. The results of finite-element analysis have shown that there are certain relationships between pole-pair numbers and torque performance. It reveals that the sum of the pole-pair numbers is inversely proportional to the maximum torque capacity; the differences of maximum torque between different pole-pair number designs could be up to 82%. However, the torque ripple has not been proven for the relationship. For future research, the torque capability per cost would be necessary for magnetic gear product, especially when the price of rare earth metal is seen rising in the past years. Also, the efficiency of magnetic gear is still important for powertrain system, but it’s not easy to reach both high torque and efficiency, owing to the flux saturation problem. The balance of torque capacity, efficiency, and cost would be the next challenge.